Verbale Aggression: multidisziplinäre Zugänge zur verletzenden Macht der Sprache - Bonacchi, Silvia; Mela, Mariusz (Diskursmuster, 2017)
"This compendium presents essays from various language-related disciplines to provide a comprehensive theoretical framework with case studies concerning verbal aggression in all its diverse forms. In this way, it gives psychologists, sociologists, educators, media scientists, and journalists scientifically based principles and perspectives for dealing with verbal aggression"--
Keywords: Aufsatzsammlung; Aggression; Gewalt; Sprache